Living with art - Getlein, Mark (McGraw-Hill Education, 2020)
"Art is part of our lives, from the monuments in our communities, to the fashions we wear and the media images we take in, to the exhibits on display in museums and galleries. It permeates our daily life. But why do we study art? How do we talk about Art? Living with Art helps students see art in everyday life by fostering a greater understanding and appreciation of art. Taking a step further, Getlein equips students with the tools necessary to analyze, digest, and uphold a life-long enthusiasm for art. "--